KARAKTERISTIK ALIRAN SUNGAI SERANG BAGIAN HILIR, PANTAI GLAGAH, KECAMATAN TEMON, KABUPATEN KULON PROGO, DIY - -, Edi Tri Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2013)
Glagah beach is a turists area of beach and lagoon on the west and the iron sand mining area on the east of Serang river embouchure in Temon Sub-District, KulonProgo District of Yogyakarta Province. Information of Serang River flow characteristics, which are also influenced by the tide of sea water would be useful for the planning of the iron sand mining, especially the impact on groundwater behavior and the management of the lagoon in relation with the estuary. The study of water flow characteristics of Serang River downstream affected by tidal sea levels have been carried out by measuring water level (TMA) in three site location, three times twenty-four hours, as well as measurements of river discharge at two points. Hydrograph analysis was then performed and the analysis of the correlation between the water level (TMA) and the river discharges. The maximum and minimum daily fluctuations occur twice a day with a three-hour span between the maximum and minimum, ie at 00.00/ 12.00 a.m or 02.00 a.m, at 12.00 p.m or at 14:0 p.m, while the minimum occurs at 06.00 a.m or 08.00 a.m and at 18:00 p.m or 20:00 p.m. The effect of sea level fluctuations on the Serang River flow is about 11.3 Km away from the estuary. Based on the result of measurement and analysis, Serang river discharge are 4 m3 per second at the upstream location (4.5 km), and 4.5 m3/second (1.3 km) from the estuary..